The Effect Market Orientation on Business Performance During the Pandemic of COVID 19 Towards MSMEs: The Mediating Role of Innovation (Study: Culinary MSMEs Lego-Lego CPI in Makassar) - Marshella Marshella; Dian Parawansa; Andi Ratna Saridewi (Hasanuddin Journal of Applied Business and Entrepreneurship, 2021)
The purpose of this study was to determine the effect of market orientation towards innovation, the effect of market orientation on business performance, the effect of innovation on the business performance and innovation mediating role of market orientation on business performance Culinary MSMEs in Makassar. This study took a sample of 36 respondents who market their product in Lego-Lego CPI city of Makassar. The analysis technique used in this study is the Partial Least Square (PLS), and Mediation / Intervening testing used Variance Accounted For (VAF). Results of market orientation hypothesis testing showed positive and significant impact on innovation, market orientation and insignificant positive effect on business performance, innovation and significant positive effect on business performance. Innovation is able to mediate the relationship of market orientation on business performance significantly. Employers culinary in Lego-Lego CPI Makassar should develop a culture of orientation on the market so as to boost innovation by adapting new ideas-oriented market changes in order to achieve improved business performance of the MSMEs during the pandemic Covid-19.